Maternal HLA genotyping is not useful for predicting severity of fetal and neonatal alloimmune thrombocytopenia. (17th October 2016) - Sainio, Susanna; Javela, Kaija; Tuimala, Jarno; Haimila, Katri
Summary: Lack of reliable laboratory parameters is the main challenge in the management of fetal and neonatal alloimmune thrombocytopenia (FNAIT). Despite the long‐known association between the HLA‐DRB3* 01:01 allele and human platelet antigen 1a (HPA‐1a) alloimmunisation, maternal human leucocyte antigen (HLA) typing has been of little clinical value. Recently, other DRB3 allele variants have been suggested to predict the severity of FNAIT. In this nationwide population‐based retrospective cohort study, we performed extensive HLA typing of 96 women, accounting for 87% of our cohort of 110 families with confirmed or possible HPA‐1a‐immunisation. The HLA type was compared with anti‐HPA‐1a levels, severity of neonatal disease and responsiveness to maternally administrated intravenous gammaglobulin (IVIG). HLA haplotypes were constructed to investigate further HLA associations. Despite significantly lower anti‐HPA‐1a levels in DRB3* 01:01‐negative women, the carrier status of this particular allele could not be used to confirm or rule out FNAIT in the absence of detectable antibodies. In the haplotype analysis, the DRB3* 01:01 allele was the actual factor associated with FNAIT. No other HLA allele was shown to be of additional value as a predictor of severe FNAIT or non‐responsiveness to IVIG treatment. Thus, HLA genotyping was not found useful in differentiating high‐ and low‐risk pregnancies or in guiding antenatal treatment in affected families.